CRISPR/Cas9‐mediated somatic correction of a novel coagulator factor IX gene mutation ameliorates hemophilia in mouse - Guan, Yuting; Ma, Yanlin; Li, Qi; Sun, Zhenliang; Ma, Lie; Wu, Lijuan; Wang, Liren; Zeng, Li; Shao, Yanjiao; Chen, Yuting; Ma, Ning; Lu, Wenqing; et al. (EMBO molecular medicine, 2016)
The X‐linked genetic bleeding disorder caused by deficiency of coagulator factor IX, hemophilia B, is a disease ideally suited for gene therapy with genome editing technology. Here, we identify a family with hemophilia B carrying a novel mutation, Y371D, in the human F9 gene. The CRISPR/Cas9 system was used to generate distinct genetically modified mouse models and confirmed that the novel Y371D mutation resulted in a more severe hemophilia B phenotype than the previously identified Y371S mutation. To develop therapeutic strategies targeting this mutation, we subsequently compared naked DNA constructs versus adenoviral vectors to deliver Cas9 components targeting the F9 Y371D mutation in adult mice. After treatment, hemophilia B mice receiving naked DNA constructs exhibited correction of over 0.56% of F9 alleles in hepatocytes, which was sufficient to restore hemostasis. In contrast, the adenoviral delivery system resulted in a higher corrective efficiency but no therapeutic effects due to severe hepatic toxicity. Our studies suggest that CRISPR/Cas‐mediated in situ genome editing could be a feasible therapeutic strategy for human hereditary diseases, although an efficient and clinically relevant delivery system is required for further clinical studies. Synopsis CRISPR/Cas9‐mediated genome editing holds promise for the treatment of genetic disorders, but its potential for hemophilia treatment is unknown. This study shows that in genome correction via Cas9 is a feasible therapeutic strategy for hemophilia B. Identification a family with hemophilia B carrying a novel mutation, Y371D, in the human F9 gene. Generation of three distinct genetically modified mouse models and confirmation that the mouse harboring the novel Y371D mutation is a new hemophilia B model. Hepatic in situ correction of the point mutation in the F9 allele via CRISPR/Cas9‐mediated genome editing was sufficient to restore hemostasis in hemophilia B mice. Graphical Abstract CRISPR/Cas9‐mediated genome editing holds promise for the treatment of genetic disorders, but its potential for hemophilia treatment is unknown. This study shows that in genome correction via Cas9 is a feasible therapeutic strategy for hemophilia B.